Ein Plädoyer für die epistemologische Semantik. Einige Überlegungen zu ihrer Konzeption, zu ihren Aufgaben und zur Analyse der polnischen Fachtextäußerungen im Fachgebiet ‚altgriechische Musik’ - Pawłowski, Grzegorz (Glottodidactica, 2015)
By way of this article the author seeks to construe epistemological semantics. To this end the author presents his arguments in several aspects as regards a) concepts, b) terms, c) subject matter, d) methods and e) analysis of expressions excerpted from texts. The author’s concept is based on hypotheses employed in anthropocentric linguistics and frame semantics. One of the building blocks of epistemological semantics is constituted by so called epistemic formants of knowledge, understood as the foundation of epistemic experience, as the base for the frames of epistemic knowledge, and hence also as the framework for the constitution of meanings and expressions formed by an individual. As important seem a strict delimitation of the subject area of epistemological semantics and the defining of resultant tasks to be undertaken by linguists. It transpires that both the subject area and the resultant tasks have up till now been restricted almost exclusively to ‘meaning’, without clear reference to the underlying cognitive acts. Methods of the work are rooted in idiocentric (individual) and polycentric (common) approaches known in linguistics. The results of the empirical analysis have been presented and exemplified by a selected specialised neologism from the field of music of Ancient Greece.